An intranasal nanoparticle STING agonist protects against respiratory viruses in animal models - Leekha, Ankita; Saeedi, Arash; Kumar, Monish; Sefat, K. M. Samiur Rahman; Martinez-Paniagua, Melisa; Meng, Hui; Fathi, Mohsen; Kulkarni, Rohan; Reichel, Kate; Biswas, Sujit; Tsitoura, Daphne; Liu, Xinli; et al. (Nature communications, 2024)
Respiratory viral infections cause morbidity and mortality worldwide. Despite the success of vaccines, vaccination efficacy is weakened by the rapid emergence of viral variants with immunoevasive properties. The development of an off-the-shelf, effective, and safe therapy against respiratory viral infections is thus desirable. Here, we develop NanoSTING, a nanoparticle formulation of the endogenous STING agonist, 2′−3′ cGAMP, to function as an immune activator and demonstrate its safety in mice and rats. A single intranasal dose of NanoSTING protects against pathogenic strains of SARS-CoV-2 (alpha and delta VOC) in hamsters. In transmission experiments, NanoSTING reduces the transmission of SARS-CoV-2 Omicron VOC to naïve hamsters. NanoSTING also protects against oseltamivir-sensitive and oseltamivir-resistant strains of influenza in mice. Mechanistically, NanoSTING upregulates locoregional interferon-dependent and interferon-independent pathways in mice, hamsters, as well as non-human primates. Our results thus implicate NanoSTING as a broad-spectrum immune activator for controlling respiratory virus infection. Respiratory viral infection causes fast onset of pathology, and is often compounded by vaccination-resistant variants. Here, the authors show that a STING agonist nanoparticle, termed NanoSTING, helps protect against SARS-CoV-2 in hamsters and influenza in mice, thereby implicating NanoSTING as a broad-spectrum treatment for respiratory viral infections.